Innovation Capability and Strategic Agility: Contributory Role on Firms’ Resilience among Tertiary Institutions in Nigeria - Banji Rildwan Olaleye; Ahmad Herzallah; Oluwaseun Niyi Anifowose (Modern Perspectives in Economics, Business and Management Vol. 6, 2021)
Purpose: The purpose of this study is to examine the relationship amongst innovation, strategic agility and firms’ resilience in Nigerian tertiary institutions. Design/Methodology/Approach: A descriptive research design was employed with a sample size of 492 top management respondents from selected tertiary institutions, using SPSS and structural equation modeling (SEM) for analysis and hypotheses testing. Findings: The authors found that innovation and strategic agility predict a firms’ resilience in tertiary institutions in Nigeria. The positive and significant path posed by innovation dimensions in relation to resilience, entails willingness of management of Nigerian tertiary institutions towards innovation, as well as reacting to changes in a timely and agile manner. Hence, university management tends to venture into ingenious pursuits such as modernized technology-based teaching resources and methodologies, as well as active and productive research development for better performance. Research Implications: Based on this study, top management members who are responsible for decision making and strategic planning should engage in inventiveness to leverage firm resilience capacity. Originality/Value: This paper complements the limited literatures on education at post-secondary level by providing a model and empirical indications on innovation being a mechanism underlying resilience capability among tertiary institutions in Nigeria.